Effect of donor/recipient body weight ratio, donor weight, recipient weight and donor age on kidney graft function in children - Špatenka, Jaroslav; Seeman, Tomáš; Foltynová, Eva; Burkert, Jan; Dušek, Jiří; Vondrák, Karel; Janda, Jan; Habrmanová, Anna; Krejčová, Jana; Matoušovic, Karel (Nephrology, dialysis, transplantation, 2012)
BACKGROUND: We hypothesized that supplementing a higher mass of renal parenchyma from adult donors, and their younger age, would improve graft function in paediatric recipients. METHODS: We calculated estimated glomerular filtration rate (eGFR; Schwartz formula) and absolute glomerular filtration rate (absGFR) in 57 renal-grafted children (1995-2007) aged 3.1-17.9 years, weighing 12.9-85.0 kg, on discharge from the hospital after transplantation (TPL), 1 year after TPL and at the last follow-up (1.5-11.7 years after TPL). We correlated their eGFR with the individual ratio between the donor and the recipient body weight at the time of TPL (donor/recipient body weight ratio; D/R BWR), and we evaluated the effect of the donor and the actual recipient body weight on the eGFR and absGFR. RESULTS: The D/R BWR varied from 0.65 to 5.23. We found a significant positive correlation between D/R BWR and eGFR at discharge from the hospital (P < 0.001), 1-year post-TPL (P < 0.001) and at the last follow-up (P < 0.05). Using multiple linear regression analyses, we found that both eGFR and absGFR values were much more determined by the actual recipient weight than by the donor weight (27/6% and 43/4% at discharge, by 24/4% and 57/0% 1 year after TPL, and 0/0% and 20/0% at the end of the follow-up). A tendency for lower eGFR with increasing age of donors was apparent at discharge and 1 year after TPL, but it reached statistical significance only at the last follow-up (r = 0.4254, P < 0.01). CONCLUSION: In paediatric renal transplants, the value of D/R BWR directly correlated with eGFR in the early and late posttransplant periods. However, this correlation was mainly influenced by the recipient weight, while the donor weight played only a minor or negligible role.
Keywords: dospělí; rejekce štěpu; dárci tkání; hodnocení rizik; Female; Graft Rejection; chronické selhání ledvin; dítě; předškolní dítě; Age Factors; Living Donors; Adult; ženské pohlaví; žijící dárci; Organ Size; Glomerular Filtration Rate; Tissue Donors; Adolescent; Time Factors; časové faktory; věkové faktory; lidé; následné studie; Risk Assessment; délka pobytu; transplantace ledvin; Kidney Failure, Chronic; kohortové studie; Length of Stay; Middle Aged; Cohort Studies; tělesná hmotnost; retrospektivní studie; Follow-Up Studies; velikost orgánu; Kidney Transplantation; Male; Child, Preschool; Kidney Function Tests; Graft Survival; Body Weight; vyšetření funkce ledvin; lidé středního věku; Child; mužské pohlaví; Retrospective Studies; přežívání štěpu; mladiství; hodnoty glomerulární filtrace; Humans